The People's Commissariat of Foreign Affairs (NKID) of the USSR in the City of Kuibyshev (1941-1943) - S. I. Chernyavsky (Vestnik MGIMO-Universiteta)
This article analyzes the work of the People's Commissariat of Foreign Affairs (NKID) of the USSR in the city of Kuibyshev (now Samara), where it was evacuated in 1941- 1943 together with other central government agencies and the diplomatic corps accredited in the USSR. Although this period was quite short, and though key decisions were, of course, made in Moscow, intense rough work was being carried out in the “reserve capital”, which ensured the solution of the tasks set by the country's leadership to the NKID apparatus.The aggression of Nazi Germany found the Soviet Union poorly prepared not only militarily, but also diplomatically. Due to the opposition of the Western powers, domestic diplomacy failed to create a collective security system to prevent the aggression of Germany, Italy and Japan. Negotiations with representatives of Great Britain and France, which were conducted in 1939, were interrupted and relations with these countries were virtually frozen.Some important strategic tasks were set before Soviet diplomacy. First of all, it was about the concentration of diplomatic activity in specific areas that could provide real assistance to the Red Army in obtaining the necessary weapons and strategic raw materials. Among other tasks were the search for allies, establishing effective military, economic and political cooperation with them, counteracting the expansion of the Nazi coalition at the expense of Sweden and Turkey, and conducting an extremely balanced policy in the Far East in order to avoid a military clash with Japan.Due to the deterioration of the military situation on the Western Front and the imminence of the capture of Moscow, on October 16, 1941, the main staff of the People's Commissariat for Foreign Affairs, headed by its Deputy Chairman A. Vyshinsky, as well as members of the diplomatic corps were evacuated to Kuibyshev (now Samara). V. Molotov and a small group of assistants remained in Moscow.The relations between the NKID and the embassies evacuated to Kuibyshev evolved differently. The level and the intensity of contacts with them largely depended on bilateral relations with the respective nations. Contacts with the embassies of Great Britain and the USA were naturally at the top of the agenda. By way of ambassadors of these countries the key tasks of forming the anti-Hitler coalition were being solved, and the dates of summit meetings were agreed upon.The crowding of the central office staff and foreign diplomats in a small regional city certainly introduced difficulties into the practical implementation of many tasks. Nevertheless, the striving for a common victory and the awareness of responsibility to their own country, united this motley crew of diplomats, and facilitated the search for compromise solutions. The return to Moscow of the employees of the People’s Commissariat and the diplomatic corps took place after the victory in the Battle of Kursk in the summer of 1943. Only at the end of 1943 Kuibyshev did finally cede its status of the capital of the USSR to Moscow.